A Different Tecnique for Head Stuck in Breech Delivery - Gürhan Güney; Nihat İnan; Aytekin Tokmak; Muammer Doğan (Medical Network, 2016)
Breech presentation and breech delivery increase fetal-maternal morbidity and mortality. In cases of fetal head stuck following delivery of the fetal body, abdominal flexion and vaginal extraction may be a choice of surgical intervention. In the current study, we report a 38-year-old, gravida 4 para 3 woman who presented in our emergency department with the fetal head remained stuck inside the uterus whereas other parts of the body were outside the vagina. Ultrasound at admission showed absent cardiac activity due to prolonged cord compression and a solid lesion 7 cm in diameter near the fetal head which was thought to be an intramural myoma was detected at the same time. Traditional maneuvers for delivery of the head under general anesthesia failed. We performed a different technique in breech delivery when all manevuers have failed. Upper flexion and lower extraction technique is a novel approach and can be performed safely by two obstetricians.